Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.chembiol.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Export Sulfur Species Required for Cytosolic tRNA Thiolation

Abstract: In eukaryotes, mitochondria have been hypothesized to generate sulfur species required for tRNA thiolation in the cytosol, although no direct evidence thus far exists. Here we have detected these sulfur species, making use of our observation that isolated yeast cytosol alone is unable to thiolate tRNAs but can do so upon addition of mitochondria. Mitochondria were found to utilize the cysteine desulfurase Nfs1 to produce sulfur-containing species with masses ranging from 700 to 1,100 Da. Mitochondria exported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…Here we show that mitochondria export an essential intermediate, called (Fe-S) int , to the cytoplasm that is then used for cytoplasmic iron-sulfur cluster assembly. However, the situation is even more complex, because another intermediate, a sulfur-only intermediate called S int , is made and exported by mitochondria and is required for cytoplasmic tRNA thiolation (39,40). The wobble uridines (U 34 ) of the cytoplasmic tRNAs specific for lysine, glutamate, and glutamine contain a thiomodification (41).…”
Section: Iron-sulfur Clusters Are Essential Cofactors Of Proteins Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we show that mitochondria export an essential intermediate, called (Fe-S) int , to the cytoplasm that is then used for cytoplasmic iron-sulfur cluster assembly. However, the situation is even more complex, because another intermediate, a sulfur-only intermediate called S int , is made and exported by mitochondria and is required for cytoplasmic tRNA thiolation (39,40). The wobble uridines (U 34 ) of the cytoplasmic tRNAs specific for lysine, glutamate, and glutamine contain a thiomodification (41).…”
Section: Iron-sulfur Clusters Are Essential Cofactors Of Proteins Inmentioning
confidence: 99%
“…Note that the pathways for biosynthesis of cytoplasmic iron-sulfur clusters and cytoplasmic tRNA thiolation possess many intersecting and overlapping features. The sulfur-only S int , like the (Fe-S) int , is also made in mitochondria in a Nfs1-dependent manner and exported to the cytoplasm via Atm1 (39,40). However, these intermediates are distinct; they are not biochemically equivalent, and they are not interchangeable.…”
Section: Iron-sulfur Clusters Are Essential Cofactors Of Proteins Inmentioning
confidence: 99%
“…Liu et al, 2014). While it is not known precisely which type of sulfur modification is directly replaced on uridine residues in eukaryotic tRNAs, mitochondrial NFS1, Isu1/2, and Atm1 in S. cerevisiae and Tum1, a persulfide mediator and activator of NFS1, have roles in forming and transporting s 2 U marks (Nakai et al, 2004;Noma, Sakaguchi, & Suzuki, 2009;Pandey et al, 2018). Moreover, the MTU1 enzyme is a mitochondrial-specific 2-thiouridylase that is a homolog of the MnmA enzyme (Black & Dos Santos, 2015;Noma et al, 2009).…”
Section: τM 5 U Is Important To Mitochondrial Trnasmentioning
confidence: 99%
“…27 Pain and coworkers discovered a 500-1000 Da sulfur-containing specie that is exported from intact mitochondria in an Atm1-dependent fashion. 29 They subsequently reported that mitochondria also export an Fe-S intermediate through Atm1 and presented evidence that the iron in the intermediate originates from mitochondria; 30 it's exciting to consider that this might be Cowan's [Fe 2 S 2 ] cluster.…”
Section: Cytosolmentioning
confidence: 99%